Snowmelt seepage fluxes of dissolved organic matter in forest and grassland – a molecular-level case study from the Hainich Critical Zone Exploratory, Germany - Huang, Chen; Schroeter, Simon A.; Lehmann, Katharina; Herrmann, Martina; Totsche, Kai Uwe; Gleixner, Gerd (Frontiers in Earth Science, 2024)
Snowfall/cover and snowmelt are essential determinants of winter soil processes/events that may force the biogeochemical dynamics of soils in temperate regions. Increasing variability of the European hydroclimate is expected to lead to more frequent intermittent warm periods, which cause snowmelt during winter and rapidly mobilize large amounts of dissolved organic matter (DOM). This study, conducted at the Hainich Critical Zone Exploratory in Germany, seeks to address a significant gap in understanding the molecular impacts of snowmelt-induced DOM flows and their ability to alter soil ecosystems rapidly. During two snowmelt events between January and March 2021, we observed that DOM concentration and composition varied more in forest soil seepage than in grassland soil seepage. Forest seepage showed a pronounced DOM flux peak and synchronous increases in the relative abundances of aromatic DOM components, indicating surface-derived transport of plant litter carbon. In the grassland, however, peak DOM fluxes were characterized by a marked increase in nitrogen-containing (N-containing) DOM components, indicating a predominance of microbial carbon. Notably, the unique DOM components specific to each ecosystem increased during peak fluxes in the forest but decreased in the grassland. We suggest that an overall higher molecular richness and the broader functional metabolic potentials in grassland may account for its relatively greater DOM stability compared to the forest during peak snowmelt events.